Penerapan Layanan Home Care Dengan Senam Lansia Dalam Mempertahankankebugaran Fisik Pada Lansia di RW 005 Kelurahan Campurejo, Kecamatan Mojoroto Kota Kediri - Siti Komariyah; Lely Khulafa’ur Rosidah; Susiani Endarwati; Widya Kusumawati (Journal of Educational Innovation and Public Health, 2023)
As the number of elderly people increases, this can cause various problems such as social, economic and health. The welfare of the elderly can be reflected through their health condition. Home Care as a form of assistance and social care for the elderly in the family or home environment can meet the needs of the elderly so that elderly exercise done regularly can prevent functional loss caused by cardiovascular disease and another benefit of this elderly exercise is that it can reduce weight and strengthens the heart muscles. Research Method: This research uses qualitative research with a pretest-posttest control design. This research was carried out in RW 005 Campurejo Village, Mojoroto District, Kediri City with a population of 20 elderly people with total sampling. Research Results: Blood pressure before and after elderly exercise also showed an average increase, namely 450.0, increasing to 750.0 with a p value of 0.004, which shows there is a significant relationship. Conclusion: there is a significant relationship between elderly exercise and physical fitness, namely blood pressure with a p value of 0.004.